Quality of Work Life of Bank Employees With Reference To Punjab National Bank, Gurugram (Haryana): Assessing and Improving the Quality of Work Life of Bank Employees at Punjab National Bank, Gurugram (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Human Resources are an organization's most valuable asset, and their proper management iscritical to its success. The quality and efficiency of an organization's human resource determines itsefficacy. Overall job satisfaction and employee involvement in the business are influenced by Quality ofWork Life (QWL). Quality of Work Life is seen as an alternative to the command and control approach topeople management. People are viewed as a 'asset' to the organisation rather than as 'costs' in the QWLapproach. It argues that allowing employees to manage their own work and make decisions improvestheir performance. The banking sector was chosen for this study because it plays a significant role inour economy. Banks have expanded to the point where they now play a substantial role in the economy.This scenario has compelled bank policymakers to investigate the underlying circumstances andexplanations, taking into account the QWL issue. Because of the importance of this industry, it isnecessary to assess the QWL of its employees. Employees may leave a job if they believe their quality ofworking life is unbalanced, in order to pursue a better QWL. Here, an attempt is made to identify theelements impacting employee quality of life, with a focus on the Punjab National Bank (PNB) inGurugram ( Haryana) and to provide appropriate recommendations for the bank to take essential steps toimprove employee quality of life.